On the Way to a Secularized Theology: Why Today’s Disapproval of an Atemporal God Is Gaining Momentum? - Vladimir K. Shokhin (Changing Societies & Personalities)
The ongoing secularization of religion, which is associated with the development of a “post-secular society,” also manifests itself in a major controversy in analytic theology, which not so long ago remained a stronghold of religious traditionalism. The belief in the inseparability of essential atemporality of the Divine from creationism, which lies at the core of Christianity and other monotheistic religions, is in the process of being revised by a growing majority of Christian theologians. The conception of a timeless God that is currently under attack by temporalist theologians is criticized as an outdated commitment on the part of traditional theology to the Neoplatonic doctrine of a “static” Absolute. However, the desire for a “static” Absolute is not limited to Greek thought but has intercultural foundations, and in reality, no contradiction between Divine activity and atemporality can be derived from the Greek, Arabic, and Indian texts dealing with it. The increasing popularity of theological temporalism is explained in terms of a scientistic attachment to evolutionism and associated urge to “democratize” a transcendent God. Some parallels from Continental “post-secular” theology, including the anthropocentric turn that replaces a theocentric vision of the world with a humanistic orientation, are also discussed.